2013
DOI: 10.24059/olj.v17i4.402
|View full text |Cite
|
Sign up to set email alerts
|

Three Institutions, Three Approaches, One Goal: Addressing Quality Assurance in Online Learning

Abstract: The rapid growth of online academic programs in higher education has prompted institutions to develop processes and implement strategies to ensure the quality of their online offerings. Although there is no “one-size-fits-all” approach, there are “quality” standards which institutions can effectively implement regardless of context. This paper examines approaches from three different types of institutions in addressing quality assurance in online education on their respective campuses. Specifically, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…The final step involved conducting thematic analyses of the students' open-ended comments; extracting related concepts and determine the dominate themes in the two learning environments. Britto et al (2014) attempted to establish benchmarks for the online educational experience from three universities, we employ a similar technique but, in an attempt, to understand the SAI from two instructors teaching the same course and using the same materials and guidelines. We did not seek to understand individual teaching differences; rather, our aim was to better understand how students perceive instruction as communicated through their completion of the open-ended section of the SAI in the two learning environments.…”
Section: Methods Proceduresmentioning
confidence: 99%
“…The final step involved conducting thematic analyses of the students' open-ended comments; extracting related concepts and determine the dominate themes in the two learning environments. Britto et al (2014) attempted to establish benchmarks for the online educational experience from three universities, we employ a similar technique but, in an attempt, to understand the SAI from two instructors teaching the same course and using the same materials and guidelines. We did not seek to understand individual teaching differences; rather, our aim was to better understand how students perceive instruction as communicated through their completion of the open-ended section of the SAI in the two learning environments.…”
Section: Methods Proceduresmentioning
confidence: 99%
“…QA processes can be established at the macro or micro levels. Macro-level QA processes manage institutional oversight; a micro level QA process may manage student experiences, such as offering support in orientating students to an online learning environment through the types of engagement tools being offered in the course delivery method [52]. Achieving quality teaching and learning is an important and complex effort involving multiple interacting levels and dimensions; these include managing the technological educational infrastructure, designing curricula and courses, training educators, and preparing students [53].…”
Section: Quality Assurancementioning
confidence: 99%
“…A comparative study suggested that although a uniform approach is absent, there are quality standards that institutions can effectively implement to address QA in online learning [52]. A QA outline that is template-and checklist-driven was proposed that is dynamically and iteratively intertwined with the e-learning development process [57].…”
Section: Quality Assurancementioning
confidence: 99%
“…To summarize, the ten rubrics reviewed in this study show similarities in the dimensions addressed and the rating scales used, but they differed in their focus for evaluation. These differences seem reasonable, as all higher education institutions have different needs, interests, and criteria for evaluating online courses (Britto, Ford, & Wise, 2013). However, from a research perspective, key questions remain: which dimensions are more important in evaluating the quality of an online course?…”
Section: Course Quality Rubricsmentioning
confidence: 99%